The Effect of Some Concentrations of Kelor Leaf Organic Powder and Planting Media Combinations on The Growth and Results of Pakcoy (Brassica rapa L.) - Syahlaa, Huuriyah; Nurmayulis; Dewi Firnia; Imas Rohmawati (Jurnal Agritechno, 2024)
The application of Moringa leaf POC is one of the best materials because it contains iron, sulfur and phosphorus which function for plant growth. Another alternative to improve pakcoy plant production is by adjusting the composition of the right planting media, for example by adding organic compost or husk charcoal. Husk charcoal is one of the planting media that functions as a soil improver and can improve soil properties. The purpose of this study was to determine the effect of several concentrations of moringa liquid organic fertilizer and the combination of planting media on the growth and yield of pakcoy (Brassica rapa L.). Data collection and processing methods using factorial group randomized design consisting of two factors. Observation data were analyzed with variance analysis (F test) at the 5% level. If there is a significantly different effect, it is continued with Duncan's Multile Range Test (DMRT) at the 0,05 level. There is an interaction between the concentration of moringa leaf POC and the combination of planting media on the parameters of plant height at 1 MST.”